2018
DOI: 10.5144/0256-4947.2018.391
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with perceptions of child sexual abuse and lack of parental knowledge: a community-based cross-sectional study from the Eastern Province of Saudi Arabia

Abstract: BACKGROUNDChild sexual abuse (CSA) has serious consequences that can affect the physical, social and mental health of a child. In the last two decades, concern about CSA has increased around the world including Saudi Arabia.OBJECTIVEEvaluate factors associated with parental perceptions and knowledge of CSA.DESIGNCross-sectional survey.SETTINGSPrimary health care clinic.SUBJECTS AND METHODSSimple random sampling was used to select participants. The main tool for data collection was a self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 27 publications
(36 reference statements)
2
20
1
6
Order By: Relevance
“…The majority of our participants have heard about child abuse, consistent with the study in Saudi Arabia where the majority of Saudi parents had adequate knowledge and perception of child abuse,[ 11 ] and also with published studies in Jordan. [ 15 16 ] About half of our parents had actually witnessed child abuse in their society.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The majority of our participants have heard about child abuse, consistent with the study in Saudi Arabia where the majority of Saudi parents had adequate knowledge and perception of child abuse,[ 11 ] and also with published studies in Jordan. [ 15 16 ] About half of our parents had actually witnessed child abuse in their society.…”
Section: Discussionsupporting
confidence: 87%
“…This is considered less than other studies where the majority of the respondents agreed that child sexual abuse is common in their community. [ 11 30 31 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several studies focusing on the perception and attitude toward child sexual abuse. Rural communities in Tanzania had accepting attitudes toward sexual violence [35] and parental responses showed that they had adequate knowledge regarding child sexual abuse [36,37]. However, most of the research has been aimed at investigating the perception and attitudes of men and women aged 18 years old and above [35,38,39], parents with children under 18 [40], or representatives of the socio-legal system (police investigators, magistrates, legal officers, and social officers) [41].…”
Section: Introductionmentioning
confidence: 99%